PERAN WALI KELAS SEBAGAI PELAKSANA BIMBINGAN KONSELING DALAM LAYANAN BELAJAR SISWA KELAS AWAL SEKOLAH DASAR - Puti Khansa, Tania; Imaningtyas, Imaningtyas; Muji Utami, Nidya Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers play an important role in supporting the transition of early-grade elementary school students into a formal educational environment. This study aims to examine the role of homeroom teachers as implementers of guidance and counseling in learning services. The method used is a Systematic Literature Review (SLR) of studies related to the role of homeroom teachers, learning guidance services, and learning difficulties among early-grade students. The data collection technique was carried out following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) flow, by documenting 25 relevant articles consisting of 12 national articles and 13 international articles. The results indicate that homeroom teachers play a major role in implementing learning guidance services, particularly in addressing learning difficulties commonly faced by early-grade elementary students, namely reading problems. Homeroom teachers provide individual and group guidance, conduct remedial programs, and collaborate with parents. However, several obstacles were identified, including time constraints, lack of counseling skills, and minimal parental support. Therefore, program planning, teacher training, and strong collaboration between schools and families are necessary to improve student learning outcomes.